Klasifikasi Kerusakan Barang Dengan Menggunakan Komparasi Algoritma C4.5 Dan Naive Bayes - Romli, Ikhsan; Kurniawan, M Edi (Yayasan Literasi Sains Indonesia, 2022)
Process control is needed to prevent goods from being damaged both in the production and delivery processes. Therefore, in this study, a classification of conditions was carried out whether the goods that experienced the incident could still be used or not. This study uses a classification model with the C4.5 and Naïve Bayes algorithms, by evaluating using the confusion matrix method, the best accuracy in the C4.5 algorithm is 73.9% recall 72.9% and 88% precision, with these results it can be said that algorithm C 4.5 is good to be implemented in this decision support system model